Analysis and optimization of the gear rattle in the parallel mode for hybrid electric vehicles - GUO Lin; LIU Xuewen; LIU Xinhao; LIN Weixiong; ZHENG Wenzhao (Jixie chuandong)
ObjectiveAiming at the abnormal noise issue in the parallel mode of a hybrid electric vehicle, its generation mechanism was investigated and optimization solutions were proposed.MethodsFirstly, vibration and noise tests were carried out on the prototype vehicle to identify the type of abnormal noise. Then, a simulation model was established to replicate parallel operating conditions, and its accuracy was verified by comparing simulation results with test data. Finally, a parameter sensitivity analysis was performed to identify the key factors influencing the noise.ResultsThe test and simulation results reveal that the abnormal noise is the gear rattle in the transmission, primarily occurring on the drive motor side. Parameters such as parallel vehicle speed, drive motor torque, and secondary flywheel inertia are found to significantly affect the issue. Validation results demonstrate that increasing the drive motor torque leads to a 66.7% reduction in vibration; elevating the parallel vehicle speed results in a 60% decrease in vibration; and augmenting the rotational inertia of the secondary flywheel yields a 46.7% reduction in vibration. The proposed solutions effectively reduce the gear rattle.